Entrepreneurial Intentions among Refugees. The Case of Syrian Refugees in Türkiye - Ion Daniel Zgura; Raluca Mariana Grosu; Ozgur Ozmen; Mirela Octavia Sirbu (Amfiteatru Economic)
Tackling an under-explored topic in the scientific literature, with high potential and of societal relevance, the paper aims at investigating the entrepreneurial intentions of Syrian refugees in Türkiye. Drawing from the experience of 50 interviewees, the research reveals a population with strong entrepreneurial intentions, often driven by past business experience, a desire for autonomy, and the need to build a stable future in the host country. Despite generally low levels of formal education and limited role models, many interviewees possessed significant self-employment experience and demonstrated resilience, motivation, and a positive outlook on risk and challenges. Entrepreneurship was broadly perceived not only as a pathway to financial independence but also as a means of achieving social status and long-term stability within the host society. However, systemic barriers, such as restricted access to capital, language obstacles, and insufficient institutional support, remain significant challenges. A smaller group within the interviewed sample expressed resistance to entrepreneurship, citing psychological distress, a preference for security and stability over uncertainty, and lack of self-confidence or experience. The paper adds to the literature, at the same time, setting guidelines for coherent policies aimed at refugees’ integration